How Safe is Progesterone? Acute Pulmonary Embolisms (APE) Alleged to Progesterone. - Dali, Bikash; Acharya, Subarna; Jha, Sunil C; Basnet, Manindra; Pradhan, Neelam; Sharma, Jyoti; Bista, Kesang Diki; Manandhar, Bekha; Rana, Ashma (Nepal Journal of Obstetrics and Gynaecology, 2011)
DOI: http://dx.doi.org/10.3126/njog.v6i1.5257 NJOG 2011; 6(1): 66-67